2023
DOI: 10.3389/fsurg.2023.1081951
|View full text |Cite
|
Sign up to set email alerts
|

Cervical lymphadenopathy as initial presentation of metastatic prostate cancer: A retrospective study of five cases and literature review

Abstract: Cervical lymphadenopathy as the initial presentation of metastatic prostate cancer is particularly uncommon, and easily misdiagnosed. In the current study, we describe five cases of metastatic prostate cancer in our hospital that presented with cervical lymphadenopathy as an initial symptom. The diagnosis was confirmed by needle biopsy of the suspicious lymph nodes and the serum prostate specific antigen (PSA) levels of all patients exceeded 100 ng/ml. The five patients were treated with hormonal therapy; four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…For such patients, the survival rates are significantly reduced. Interestingly, owing to the underlying widespread metastatic disease, cervical lymphadenopathy has a rather strong association with PSA levels beyond 100 ng/ml; with 26 / 29 patients (89.6%) satisfying this biochemical finding [8]. Even in the current case, our patient had a PSA level of 364.8 ng/ml at time of presentation.…”
Section: Discussionmentioning
confidence: 44%
“…For such patients, the survival rates are significantly reduced. Interestingly, owing to the underlying widespread metastatic disease, cervical lymphadenopathy has a rather strong association with PSA levels beyond 100 ng/ml; with 26 / 29 patients (89.6%) satisfying this biochemical finding [8]. Even in the current case, our patient had a PSA level of 364.8 ng/ml at time of presentation.…”
Section: Discussionmentioning
confidence: 44%
“…It is interesting to note that only 7 of the 58 patients presented with right‐sided supraclavicular lymphadenopathy since more commonly, retrograde lymphatic spread via the left jugular trunk leads to the left‐sided cervical lymph nodes. 5 Though we obtained biopsies only from the right supraclavicular node and prostate, the distribution of other enlarged lymph nodes and their decrease in size following androgen deprivation therapy, together with decline in PSA from 121 ng/mL to 1.3 ng/mL favors the assumption that the generalized lymphadenopathy was secondary to metastatic spread and not any other secondary or additional diagnosis. COVID‐19 vaccination has been noted to be safe and effective in the elderly with lower adverse events reported compared to younger populations.…”
Section: Discussionmentioning
confidence: 92%
“…In a recent literature review, Liu et al note that 58 cases have been reported where cervical lymphadenopathy is the initial presentation of metastatic prostate cancer. It is interesting to note that only 7 of the 58 patients presented with right‐sided supraclavicular lymphadenopathy since more commonly, retrograde lymphatic spread via the left jugular trunk leads to the left‐sided cervical lymph nodes 5 . Though we obtained biopsies only from the right supraclavicular node and prostate, the distribution of other enlarged lymph nodes and their decrease in size following androgen deprivation therapy, together with decline in PSA from 121 ng/mL to 1.3 ng/mL favors the assumption that the generalized lymphadenopathy was secondary to metastatic spread and not any other secondary or additional diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent literature review, Liu et al note that 58 cases have been reported where cervical lymphadenopathy is the initial presentation of metastatic prostate cancer. It is interesting to note that only 7 of the 58 patients presented with right-sided supraclavicular lymphadenopathy since more commonly, retrograde lymphatic spread via the left jugular trunk leads to the left-sided cervical lymph nodes [5]. Though we obtained biopsies only from the right supraclavicular node and prostate, the distribution of other enlarged lymph nodes and their decrease in size following androgen deprivation therapy, together with decline in PSA from 121ng/ml to 1.3 ng/ml favors the assumption that the generalized lymphadenopathy was secondary to metastatic spread and not any other secondary or additional diagnosis.…”
Section: Discussionmentioning
confidence: 99%